2021
DOI: 10.1002/cphc.202100527
|View full text |Cite
|
Sign up to set email alerts
|

Rational Development of a Metal‐Free Bifunctional System for the C−H Activation of Methane: A Density Functional Theory Investigation

Abstract: The activation or heterolytic splitting of methane, a challenging substrate usually restricted to transition metals, has so far proven elusive in experimental frustrated Lewis pair (FLP) chemistry. In this article, we demonstrate, using density functional theory (DFT), that 1-aza-9-boratriptycene is a conceptually simple intramolecular FLP for the activation of methane. Systematic comparison with other FLP systems allows to gain insight into their reactivity with methane. The thermodynamics and kinetics of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…However, with the prediction of 9-phosphatriptycenes p K a ’s, this study has demonstrated that the same result can also be obtained by only changing structural parameters. In our research group, this strategy was already successfully applied to enhance the reactivity of triarylboranes, developing a new family of nonplanar Lewis acids. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with the prediction of 9-phosphatriptycenes p K a ’s, this study has demonstrated that the same result can also be obtained by only changing structural parameters. In our research group, this strategy was already successfully applied to enhance the reactivity of triarylboranes, developing a new family of nonplanar Lewis acids. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Tight convergence thresholds were used for geometry optimizations, for example, for the residual forces on the atoms, it is 1.5 × 10 –5 Hartree/Bohr or Hartree/radian. This method was shown previously to give satisfactory results in thermochemistry when compared to higher-level methods such as double-hybrid DFT with a more extended and flexible basis set . Calculations were performed at the temperature and pressure of 298.15 K and 1 atm, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formal replacement of the CH group in the aromatic ring of B­(C 6 H 4 ) 3 CH by the nitrogen atom results in 1-aza-9-boratriptycene, which may be considered an intramolecular FLP. Its reactivity toward C–H activation was computationally explored …”
Section: Introductionmentioning
confidence: 99%
“…Its reactivity toward C−H activation was computationally explored. 29 The data on Lewis acidity of 9-boratriptycene vary depending on the used LA scale. The Gutmann acceptor number 30 of 9boratriptycene (76 26 ) is slightly smaller than that of B(C 6 F 5 ) 3 (76−82 31 ), indicating that 9-boratriptycene is a weaker LA than B(C 6 F 5 ) 3 with respect to triethylphosphineoxide.…”
Section: ■ Introductionmentioning
confidence: 99%